1997
DOI: 10.1161/01.cir.96.4.1180
|View full text |Cite
|
Sign up to set email alerts
|

Histological Substrate of Atrial Biopsies in Patients With Lone Atrial Fibrillation

Abstract: Abnormal atrial histology was uniformly found in multiple biopsy specimens in all patients with LAF. It was compatible with a diagnosis of myocarditis in 66% of patients (active in 25%) and of noninflammatory localized cardiomyopathy in 17% and was represented by patchy fibrosis in 17%. The cause of the pathological changes, which were found only in atrial septal biopsies but not in biventricular biopsies, in 75% of patients remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
855
2
34

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,256 publications
(916 citation statements)
references
References 13 publications
25
855
2
34
Order By: Relevance
“…It should be emphasized that previous studies did not compare the role of inflammation in valvular AF and nonvalvular AF. 3,4,6,8 This study is the first to report the correlation of nonvalvular AF with elevated expression of markers of systemic inflammation, such as TNF-α mRNA, IL-6 mRNA in peripheral blood monocytes, and serum IL-1.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It should be emphasized that previous studies did not compare the role of inflammation in valvular AF and nonvalvular AF. 3,4,6,8 This study is the first to report the correlation of nonvalvular AF with elevated expression of markers of systemic inflammation, such as TNF-α mRNA, IL-6 mRNA in peripheral blood monocytes, and serum IL-1.…”
Section: Discussionmentioning
confidence: 86%
“…3,4 Furthermore, Frustaci et al reported that inflammatory infiltrates and oxidative damage were uniformly found in multiple biopsy specimens in 12 patients with paroxysmal lone AF refractory to conventional antiarrhythmic treatment. 8 Inflammation may promote the persistence of AF and hypertension, but the mechanism is poorly understood and needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…26 Inflammatory changes have been observed in atrial tissues obtained from patients with isolated persistent AF. 27 Serum CRP level has been found to be significantly higher in patients with paroxysmal and chronic AF than in normal controls. 9 In a retrospective analysis of the Cardiovascular Health Study, it was shown that higher inflammation status during sinus rhythm potentially increases the risk of occurrence of AF in a follow-up period.…”
Section: Discussionmentioning
confidence: 96%
“…31,32 Frustaci et al first demonstrated a high prevalence of inflammatory infiltrates, myocyte necrosis and fibrosis in atrial biopsies from patients with lone AF, but not in atrial biopsies from control patients. 33 Other papers have reported that an increase in high-sensitivity C-reactive protein levels is an independent risk factor for future AF among patients with sinus rhythm. 34,35 Whether inflammation is a consequence or a cause of AF is still controversial.…”
Section: Discussionmentioning
confidence: 99%